2000
DOI: 10.1063/1.126277
|View full text |Cite
|
Sign up to set email alerts
|

Improved tip performance for scanning near-field optical microscopy by the attachment of a single gold nanoparticle

Abstract: Nanometer-size optical probes are gaining increasing interest in near-field optical microscopy. Optimization of the probe shape is still a challenging research and development issue. Here, we propose to improve the optical properties of a fiber-based probe by attachment at the tip apex of one single gold particle of 60 nm diameter. This probe produces an enhancement of the light throughput, both in the near and the far fields, a homogenization of the diffracted light polarization, and a higher accuracy of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
31
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 11 publications
1
31
0
Order By: Relevance
“…This may be related to the fact that the smaller the aperture, the larger the portion of the evanescent component in the light out of the SNOM probe and, thus, the more efficient the excitation of SPPs. And the fact that Au coating on the probe apex shows the highest efficiency of EM energy transportation is also consistent with the previous experimental result of Kim et al, which suggested that Au or Ag coating on the SNOM probe apex enhances the efficiency of SPP excitation (Kim et al, 2003a;Sqalli et al, 2000).…”
supporting
confidence: 90%
“…This may be related to the fact that the smaller the aperture, the larger the portion of the evanescent component in the light out of the SNOM probe and, thus, the more efficient the excitation of SPPs. And the fact that Au coating on the probe apex shows the highest efficiency of EM energy transportation is also consistent with the previous experimental result of Kim et al, which suggested that Au or Ag coating on the SNOM probe apex enhances the efficiency of SPP excitation (Kim et al, 2003a;Sqalli et al, 2000).…”
supporting
confidence: 90%
“…Such phenomena could lead to a material selective trapping. It will also be interesting to explore the possibility of trapping a small gold particle, a few nanometers in size, and use it as a highly localized probe for topographic or spectroscopic studies 29,30 .…”
Section: Discussionmentioning
confidence: 99%
“…4,5 Recently a very innovative design that combines nearfield optical probes with a cantilever ͓atomic force microscopy-scanning near field optical microscopy ͑SNOM͒ hybrid probes͔ has been proposed. In this approach, the probes comprise a 12 m high amorphous SiO 2 conical nearfield tip on a silicon cantilever.…”
mentioning
confidence: 99%